Forage chemistry and the digestive system in reindeer (Rangifer tarandus tarandus) in northern Norway and on South Georgia - Mathiesen, Svein D.; Aagnes Utsi, Tove H.; Sørmo, Wenche (Rangifer, 1999)
Comparative chemical and botanical analyses of the reticulo-rumen content (RR) and the fill of the digestive system were carried out in free-living Norwegian reindeer {Rangifer t. tarandus) on South Georgia (SG) in summer (mean body mass (BM) = 74 kg, n - 10), and in northern Norway in late summer (NS) (mean BM = 77 kg, n = 6) and winter (NW) (mean BM = 60 kg, n = 11). The RR of SG reindeer contained mainly grasses, while grasses dominated in NS reindeer and woody plants and lichens in NW reindeer. Mean ruminal plant cell-wall contents (CWC) comprised 37% of organic dry matter (OM) in SG reindeer and 50 and 69% in NS and NW reindeer, respectively. The high CWC in NW reindeer was due to high intake of lichens containing as much as 45% hemi-cellulose. Mean ruminal content of lignin was as low as 5% of OM in SG reindeer, which was different (P < 0.05) from NS (14%) and NW reindeer (15%), respectively. The mean total gastro-inresrinal tract (GIT) (fill and tissue) weight was 27% of BM in SG reindeer, different (P < 0.05) from NS (18% of BM) and NW reindeer (22% of BM), respectively. Wet weight RR content was 14.5% of BM in SG reindeer, not different from NS (12.2% of BM) and NW reindeer (14.2% of BM). The ratio between the wet weight content of the distal fermentation chamber (DFC) and the RR wet weight content was 1:10 in SG reindeer, different (P < 0.05) from NS (1:14) and NW reindeer (1:14). We did not find any significant differences between the intestinal lengths of the groups investigated. It was concluded that the degree of fill of the different parts of GIT in reindeet seems to be related to the lignin content of plants eaten and not only of seasonal changes in appetite and availability of plants. Our data stress the fact that reindeer are highly adaptable to a wide range of different dietary plants, even in the southern hemisphere.